The last movie - Hopper, Dennis 1936-2010; Stern, Stewart 1922-2015 (Powerhouse films ltd., 2019)
"In der Wildnis der Anden wird ein Hollywood-Western gedreht. Die peruanischen Eingeborenen schauen staunend zu, ohne zu begreifen, dass die wüsten Schießereien nur gestellt sind. Nachdem die Produktion wieder abgezogen ist, spielen die Indios selbst "Filmproduktion"; sie prügeln sich dabei allerdings ganz real. Ein Stuntman, der bei ihnen geblieben ist, wird angeschossen, als er einzugreifen versucht. Ein wild verschachtelter und mit einer Vielzahl experimenteller Einfälle durchsetzter Film über den Mythos Film; zugleich eine wütende Abrechnung mit dem Hollywood-System." [filmdienst.de]
Original: USA 1971
Bildformat 1.85:1
limited edition blu-ray special features: 4K restoration from the original negative ; original mono audio ; the Guardian interview with Dennis Hopper (1990, 91 mins): archival audio recording of the filmmaker and actor in conversation with critic Derek Malcolm at London’s National Film Theatre ; Dennis Hopper Video Introduction (2007, 2 mins) ; Scene Missing (2012, 50 mins): documentary directed by Alex Cox on the making of The last movie ; Some kind of genius (1986, 30 mins): Paul Joyce’s documentary portrait of Dennis Hopper ; Postcards from Peru (2018, 32 mins): new interviews with members of the Peruvian cast and crew ; 8mm on-set footage (1970, 10 mins, silent): rare and previously unseen material shot on location by actors John Phillip Law and Victor Maymudes ; The Dick Cavett Show (1971, 7 mins): extract from the popular US chat show, featuring an interview with Hopper ; Restoration Demonstration (3 mins) ; 1971 product reel ; original 1971 theatrical trailer ; 2018 UK re-release trailer ; image gallery: on-set and promotional photography ; new and improved English subtitles for the deaf and hard-of-hearing ; limited edition exclusive 80-page book containing extensively researched new writing by filmmaker Alex Cox, rare archival photography, and full film credits ; limited edition exclusive double-sided poster ; UK premiere on blu-ray ; limited edition of 3,000 copies
Keywords: Film; Blu-Ray-Disc